2004
DOI: 10.2337/diacare.27.10.2429
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Syndrome Defined by Factor Analysis and Incident Type 2 Diabetes in a Chinese Population With High Postprandial Glucose

Abstract: OBJECTIVE -The aim of this study was to examine how the major components of the metabolic syndrome relate to each other and to the development of diabetes using factor analysis.RESEARCH DESIGN AND METHODS -The screening survey for type 2 diabetes was conducted in 1994, and a follow-up study of nondiabetic individuals at baseline was carried out in 1999 in the Beijing area. Among 934 nondiabetic and 305 diabetic subjects at baseline, factor analysis was performed using the principle components analysis with var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 35 publications
4
42
2
Order By: Relevance
“…However, several putative mechanisms can be proposed. The obesity-related insulin-resistance syndrome, which describes a cluster of metabolic abnormalities (insulin resistance, hypertension, dyslipidaemia and impaired glucose regulation), has been recognised to play an important role in the development of type 2 diabetes [36][37][38][39][40]. A high intake of dietary sodium and the high urinary sodium to potassium ratio have been shown to have a direct relationship with essential hypertension [10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…However, several putative mechanisms can be proposed. The obesity-related insulin-resistance syndrome, which describes a cluster of metabolic abnormalities (insulin resistance, hypertension, dyslipidaemia and impaired glucose regulation), has been recognised to play an important role in the development of type 2 diabetes [36][37][38][39][40]. A high intake of dietary sodium and the high urinary sodium to potassium ratio have been shown to have a direct relationship with essential hypertension [10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…As shown, all of the studies (24,33,38, [143][144][145][146][147][148][149] found that at least two and usually three to four factors underlie the overall correlation between risk variables, even though different factor analysis methods were used. Shen et al (150), using "confirmatory factor analysis," which provides some advantages and is complementary to exploratory factor analysis, proposed a correlated four-factor model that nicely depicts the major factors related to the syndrome (Fig.…”
Section: Does the Syndrome Reflect A Single Underlying Pathological Pmentioning
confidence: 99%
“…As shown, all of the studies [24,33,38,[143][144][145][146][147][148][149] found that at least two and usually three or four factors underlie the overall correlation between risk variables, even though different factor analysis methods were used. Shen and colleagues [150] using 'confirmatory factor analysis', which provides some advantages and is complementary to exploratory factor analysis, proposed a correlated four factor model that nicely depicts the major factors related to the syndrome (Fig.…”
Section: Does the Syndrome Reflect A Single Underlying Pathological Pmentioning
confidence: 99%